2022
DOI: 10.3389/fenvs.2022.972328
|View full text |Cite
|
Sign up to set email alerts
|

The impact of environmental subsidy on the performance of corporate environmental responsibility: Evidence from China

Abstract: Corporate environmental responsibility (CER) has become a critical factor for measuring the competitiveness of firms in China, and environmental subsidies may be a catalyst for promoting firms’ CER. This study uses data from Chinese A-share listed firms during 2010–2020. Using the instrumental variable two-stage least squares (IV-2SLS) method, we found that environmental subsidies significantly improve corporate environmental performance but have no significant impact on the disclosure and governance of pollut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In this paper, the Jacobi matrix is constructed by referring to Jiang et al [63], as shown in Equation (9). The stability of the equilibrium point of the replicated dynamic system can be obtained by analyzing the local stability of the Jacobi matrix.…”
Section: Evolutionary Equilibrium Stability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, the Jacobi matrix is constructed by referring to Jiang et al [63], as shown in Equation (9). The stability of the equilibrium point of the replicated dynamic system can be obtained by analyzing the local stability of the Jacobi matrix.…”
Section: Evolutionary Equilibrium Stability Analysismentioning
confidence: 99%
“…Government green development behavior is an important initiative to address environmental management challenges, which mainly include incentive green development behavior and mandatory green development behavior [8]. Among them, incentives for green development behaviors include granting environmental subsidies and issuing tax breaks [9], promoting green consumption [10], etc. In contrast, strict regulation of the market and the issuance of mandatory and catalog regulations are mandatory green development behaviors [11].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental regulations (ERs) are an important means of reducing environmental pollution [2]. The public demands that the government introduce appropriate policies to deal with environmental pollution [3], and that companies take up their own corporate social responsibility, increase their environmental investment, and enhance their environmental efficiency [4]. Corporations can mitigate environmental pollution by enhancing production efficiency and upgrading through innovation in green technology [5].…”
Section: Introductionmentioning
confidence: 99%